Islamic Eco-Theology-Based Environmental Education: Integrating Divine Values to Foster Ecological Awareness and Environmental Ethics in Students - Miranda Anggraini; Muhamad Sholihin; Asmuni (Edumaspul: Jurnal Pendidikan, 2025)
Conventional environmental education often fails to translate ecological knowledge into sustainable behavioral change due to a lack of moral and spiritual dimensions. This study aims to explore the integration of Islamic eco-theology into environmental education to foster ecological awareness and akhlaq (moral character) towards nature among students. Employing a qualitative narrative literature review, data were synthesized from peer-reviewed articles published between 2019 and 2024 via Google Scholar. The findings reveal that grounding environmental science in theological concepts—such as Khalifah (vicegerency), Amanah (trust), and Mizan (balance)—shifts students’ perspectives from anthropocentrism to theocentric stewardship. Furthermore, combining formal curriculum integration, experiential learning like Tadabbur alam, and a green hidden curriculum effectively translates cognitive awareness into tangible pro-environmental behaviors. Ultimately, embedding eco-theology into educational frameworks transforms environmental conservation from a secular duty into a profound spiritual obligation, providing a robust model for Islamic schools to cultivate ecologically responsible generations.